An Empathetic Added Sustainability Index (EASI) for cementitious based construction materials. (20th May 2019) - Coppola, L.; Coffetti, D.; Crotti, E.; Gazzaniga, G.; Pastore, T.
Abstract: The concrete industry is the largest consumer of natural resources and the Portland cement, the binder of modern concrete mixtures, is not environmentally friendly. The world's cement production, in fact, contributes to the earth's atmosphere about 5–7% of the total CO2 emissions, CO2 being mainly responsible for global warming and climate change. As a consequence, concrete industry in the future has to feed the growing population needs – expected to rise up to ten billion in 2050 - being sustainable by means of the "3R-Green Strategy": Reduction in consumption of gross energy, Reduction in polluting emissions and Reduction in consuming not renewable natural resources. At the same time, the concept of sustainable development in the concrete industry is not well defined and, currently, there are no holistic models capable of assessing the environmental footprint of cement-based materials. For this reason, a new Empathetic Added Sustainability Index (EASI) was developed taking into account both the environmental impact of mortars and concretes through the global warming potential (GWP), the gross energy requirement (GER) and the natural raw materials consumption (NRMC) but also the durability performance and the engineering performance (such as compressive and tensile strength, bond to reinforcing steel, shrinkage and creep, shear properties, etc) required as a function of the specific application. EASI demonstrated that Alkali Activated Slag (AAS) and High Volume Fly Ash (HVFA) reinforced concretes are characterized by the lower environmental impact in chloride-rich environments. On the other hand, in CO2 -rich environments, the best solution in terms of sustainability is represented by the HVFA concretes. Finally, for a thermal plaster exposed to freeze and taw cycles, EASI clearly showed that AAS lightweight plaster is the most appropriate solution.